Locoregional treatment of breast cancer during pregnancy - Toesca, Antonio (Gynecol Surg, 2014)
The management of patients with breast cancer during pregnancy is very demanding and it should be better performed in highly qualified and experienced centers. Referral to institutes and physicians trained in this special clinical scenario allows reducing the risk of both overtreating and undertreating the patients. Moreover, patients can receive appropriate information regarding safety of treatments without old-fashioned taboo. The purpose of the current paper is to discuss the main issues concerning surgical management and in general locoregional treatment of patients diagnosed with breast cancer and treated during gestation, focusing on those women who chose to continue their pregnancy. We cover the issues regarding type of breast surgery, radiation therapy, immediate reconstruction during mastectomy, and management of the axilla.